Ejtm3 experiences after ChatGPT and other AI approaches: values, risks, countermeasures - Giorgio Fanò-Illic; Daniele Coraci; Maria Chiara Maccarone; Stefano Masiero; Marco Quadrelli; Aldo Morra; Barbara Ravara; Amber Pond; Riccardo Forni; Paolo Gargiulo (European Journal of Translational Myology)
We invariably hear that Artificial Intelligence (AI), a rapidly evolving technology, does not just creatively assemble known knowledge. We are told that AI learns, processes and creates, starting from fixed points to arrive at innovative solutions. In the case of scientific work, AI can generate data without ever having entered a laboratory, (i.e., blatantly plagiarizing the existing literature, a despicable old trick). How does an editor of a scientific journal recognize when she or he is faced with something like this? The solution is for editors and referees to rigorously evaluate the track records of submitting authors and are doing. For example, false color evaluations of 2D and 3D CT and MRI images have been used to validate functional electrical stimulation for degenerated denervated muscle and a home Full-Body In-Bed Gym program. These have been recently published in Ejtm and other journals. The editors and referees of Ejtm can exclude the possibility that the images were invented by ChatGPT. Why? Because they know the researchers: Marco Quadrelli, Aldo Morra, Daniele Coraci, Paolo Gargiulo and their collaborators as well! Artificial intelligence is not banned by the EJTM, but when submitting their manuscripts to previous and to a new Thematic Section dedicated to AI in Translational Mobility Medicine authors must openly declare whether they have used artificial intelligence, of what type and for what purposes. This will not avoid risks of plagiarism or worse, but it will better establish possible liabilities.